Class and power in Roman Palestine: the socioeconomic setting of Judaism and Christian origins - Keddie, Anthony ca. 20./21. Jh. (Cambridge University Press, 2019)
Examines how socioeconomic relations between Judaean elites and non-elites changed as Palestine became part of the Roman Empire.